Pencitraan radiologik CT-scan sebagai alat screening pasien untuk pemasangan implan gigi Radiologic imaging of CT-scan as a screener for patients in placing dental implant - Barunawaty Yunus; Syamsiar Toppo (DiscoverSys Inc., 2012)
The success of dental implant installment is determined by the condition of alveolar bone itself. Although there is nolegal research of the dental implant treatment failure in Indonesia, but there are some reports which state that thereis a lot of dental implant treatment failure happened which caused by the lack of appraisal of the quality andquantity of the alveolar bone image which is accurate and optimal in the usement of radioghraphy units. But as thetime goes, the public needed of dental implant treatment begins increased. The purpose of this paper is to introducethe CT-Scan with Hounsfield Unit sofe ware as a screener to patients for dental implant placement with value bonemineral density (BMD). The measurement of BMD on alveolar bone before surgery for dental implant installmentmust describe local condition and then compared the size with the diameter of dental implant. From the discussion,it can be concluded that with using the CT-Scan, somebody can be stated get requirement or not for dental implantplacement.